Spicy Spicy Hot! - Wen, Lenny (New York, 2023)
Lintang is determined to embrace the spice of sambal in order to connect with her Indonesian grandmother and heritage.
Ages 4-8.
Keywords: Food habits -- Juvenile fiction; Cooking, Indonesian -- Juvenile fiction; Grandmothers -- Juvenile fiction; Food habits -- Fiction; Cooking, Indonesian -- Fiction; Grandmothers -- Fiction; Picture books